2004
DOI: 10.2174/1568009043481614
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is a Critical Cellular Event in Cancer Chemoprevention and Chemotherapy by Selenium Compounds

Abstract: Epidemiological studies, preclinical investigations and clinical intervention trials support the role of selenium compounds as potent cancer chemopreventive agents; the dose and the form of selenium are critical factors in cancer prevention. Induction of apoptosis and inhibition of cell proliferation are considered important cellular events that can account for the cancer preventive effects of selenium. Toxicity should always be considered a determining factor in the selection of potential chemopreventive agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
196
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(206 citation statements)
references
References 130 publications
7
196
0
3
Order By: Relevance
“…MSeA has been shown to be an effective anticancer agent in several in vitro and in vivo prostate cancer models and is known to induce growth arrest and apoptosis. 29,38,39 In our study, ex vivo MSeA treatment of PAIII cells resulted in significant reduction in the tumor weights in LW rats. More importantly, upon oral MSeA treatment, the number of metastatic lung foci was significantly reduced.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…MSeA has been shown to be an effective anticancer agent in several in vitro and in vivo prostate cancer models and is known to induce growth arrest and apoptosis. 29,38,39 In our study, ex vivo MSeA treatment of PAIII cells resulted in significant reduction in the tumor weights in LW rats. More importantly, upon oral MSeA treatment, the number of metastatic lung foci was significantly reduced.…”
Section: Discussionsupporting
confidence: 51%
“…[22][23][24][25][26][27][28] The majority of the inhibitory effects of selenium compounds involve apoptosis as a critical event, and several effective organic selenium compounds including seleno-keto acids have been reviewed on the basis of their apoptotic potential in several cancer models including prostate cancer. 29,30 A promising anticancer agent methylseleninic acid (MSeA) has been shown to be effective in inhibiting prostate cancer growth in vitro and in TRAMP model. 31,32 However, the potential of MSeA as a therapeutic agent has not been tested in humans, and the underlying mechanism(s) of selenium compounds including MSeA have not been studied in hypoxic conditions.…”
mentioning
confidence: 99%
“…A reasonable hypothesis is that selenium compounds act as suppressing agents, possibly by inducing apoptosis and inhibiting cell proliferation [20]. Consistent with this hypothesis, we showed that p-XSC induces Fas-L/JNK-dependent apoptosis in oral cancer cells [21].…”
Section: Introductionsupporting
confidence: 57%
“…Further understanding of the chemotherapeutic mechanisms of candidate compounds may provide a rational approach to using such agents to enhance apoptosis as a strategy for effective chemoprevention of cancer (20). Accumulating evidence supports the hypothesis that apoptosis is a critical mechanism in cancer chemoprevention by Se-containing compounds (21). The synthetic Se-enriched chemotherapeutic polysaccharide κ-selenocarrageenan might inhibit proliferation of K562/ADM cells and induce apoptosis via a Fascaspase-3 pathway (22).…”
Section: Discussionmentioning
confidence: 91%